PENGENALAN PERMAINAN BOLA MATEMATIKA PADA KELAS V SD INPRES KOTA RAJA - Jonner Nainggolan; Abraham Abraham; Fitriani Tandililing (JURNAL PENGABDIAN PAPUA, 2019)
The problems in elementary schools in Papua, not yet achieving KKM mathematics lessons, this is due to the lack of interest and motivation of students learning mathematics. The cause of the lack of interest and motivation of students learning mathematics is due to the lack of innovation in the mathematics learning method used by mathematics teachers. One innovative learning method is a mathematical game, with the game method students feel learning while playing and that is fun, so students will be interested in learning mathematics. This activity was carried out in class V of Kota Raja Jayapura Inpres Elementary School which was held on September 3, 2018. At the time of the activity the participants were very enthusiastic. The pre-test results obtained an average value of 47.27 while the post-test obtained an average value of 53.33 with an increase in N-Gain of 0.17.Keywords: Games, math ball, learning methods, N-gain